Pelaksanaan Kegiatan iHT Dengan Aplikasi Google Meeting Untuk Meningkatkan Kemampuan Guru Menyusun RPP Daring Masa Pandemi COVID 19 - Sabam Harianja (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2022)
This research is School Action Research (PTS). The research subjects were 14 subject teachers at SMAN 1 Lintongnihuta. Data collection techniques using observation and documentation techniques. Data validation with triangulation technique. Data analysis used qualitative data analysis techniques. Based on the data analysis of the results of the IHT implementation with the Google Meeting application, it was proven to be able to improve the ability of teachers in preparing Online RPP during the Covid 19 Pandemic. In the initial conditions the average score was 48.48 and was included in the Less (K) category, increasing in the first cycle with an average of 48.48 the average value is 73.30 and is included in the Enough (C) category and in the second cycle with an average value of 90.63 and is in the Good (B) category. As for improving the ability of teachers at SMAN 1 Lintongnihuta in compiling Online RPP for the Covid-19 Pandemic Period individually, in the initial conditions there were no teachers who were declared complete, in the first cycle 8 teachers or 57.14% were declared complete and in the second cycle 14 teachers or 100% were declared complete. finished.